PENGARUH REBUSAN DAUN SUKUN TERHADAP KONTROL KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS DI DESA AIKMEL - Baiq Fina Farlina; Suhaemi Suhaemi (Sekolah Tinggi Pariwisata Mataram, 2021)
In lowering blood sugar levels for patients haves DM can be done by means of herbal treatment, the types of plants that can be used as herbal medicine are: Brotowali, Aloe vera, Noni and Pare. In addition to herbal remedies that are on top there is one more plant that can lower glucose levels high leaves Breadfruit, therefore researcher is interested to study about Breadfruit leaves. this research, consists of two variables namely; independent variable (a decoction of the breadfruit leaf) and the dependent variable (diabetes mellitus). By using quasi-experimental research design with one group pretest-posttest design of the samples are 30 peoples. With the collection of data using the research instrument (a check list) which is then analyzed by using tabulation